2005
DOI: 10.1534/genetics.104.035915
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Selection in the Wild: Testing Population Genetics Theory of Self-Incompatibility in the Rare SpeciesBrassica insularis

Abstract: Self-incompatibility (SI) systems are widespread mechanisms that prevent self-fertilization in angiosperms. They are generally encoded by one genome region containing several multiallelic genes, usually called the S-locus. They involve a recognition step between the pollen and the pistil component and pollen is rejected when it shares alleles with the pistil. The direct consequence is that rare alleles are favored, such that the S-alleles are subject to negative frequency-dependent selection. Several theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
102
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(116 citation statements)
references
References 61 publications
11
102
1
1
Order By: Relevance
“…This observation of increasing numbers of S alleles with increasing dominance level is in accordance with both theoretical expectations (Schierup et al, 1997;Schierup, 1998;Uyenoyama, 2000;Billiard et al, 2007) and empirical observations (Kowyama et al, 1994;Glemin et al, 2005;Prigoda et al, 2005;Schierup et al, 2006) for SSI systems with multiple S allele dominance classes. This difference in S allele diversity, dependant on the relative dominance level of individual S alleles, is due to stronger negative frequency-dependent selection acting upon more dominant S alleles because their S phenotypes are more frequently expressed and exposed to selection in different S genotype combinations than more recessive S alleles.…”
Section: S Allele Dominance Interactionssupporting
confidence: 90%
See 2 more Smart Citations
“…This observation of increasing numbers of S alleles with increasing dominance level is in accordance with both theoretical expectations (Schierup et al, 1997;Schierup, 1998;Uyenoyama, 2000;Billiard et al, 2007) and empirical observations (Kowyama et al, 1994;Glemin et al, 2005;Prigoda et al, 2005;Schierup et al, 2006) for SSI systems with multiple S allele dominance classes. This difference in S allele diversity, dependant on the relative dominance level of individual S alleles, is due to stronger negative frequency-dependent selection acting upon more dominant S alleles because their S phenotypes are more frequently expressed and exposed to selection in different S genotype combinations than more recessive S alleles.…”
Section: S Allele Dominance Interactionssupporting
confidence: 90%
“…No such constraints apply to SSI in which complex S allele dominance interactions are possible in both pollen and pistil, thereby introducing an additional level of mating system complexity relative to GSI (Schierup et al, 1997). Within SSI systems, different kind of dominance interactions are possible, including complete dominance and tissue-specific dominance, and S alleles can often be ranked into a dominance hierarchy consisting of dominance classes of S alleles with codominant interactions between alleles within the group and dominance interactions between alleles from different groups (for example, Ockendon, 1974;Kowyama et al, 1994;Mehlenbacher, 1997;Glemin et al, 2005). S alleles that are frequently recessive in S allele interactions (hereafter referred to as recessive S alleles) are subject to less intense negative frequencydependent selection than dominant or codominant S alleles leading to a 'recessive effect' whereby recessive S alleles are more frequent within populations than more dominant S alleles (Sampson, 1974;Schierup, 1998;Billiard et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brassica insularis, Glémin et al (2005) compared the population structure at the S-locus with that indicated by selectively neutral loci, nuclear simple sequence repeats (SSRs or microsatellites); their data supported most of the theoretical predictions. In Senecio squalidus, spatial genetic structure within populations was found to be weak at both the S-locus and at allozyme loci for which variation seemed to be selectively neutral (Brennan et al, 2003), whereas genetic differentiation among populations was smaller at the S-locus than at the allozyme loci (Brennan et al, 2006).…”
Section: Introductionmentioning
confidence: 79%
“…A low population genetic structure at the S-locus is thus expected, even under very restricted migration (Schierup et al, 2000;Muirhead, 2001). These predictions have been tested in natural populations, and the results showed that the S-locus has indeed a lower genetic differentiation among populations than neutral loci (Glémin et al, 2005;Schierup et al, 2008;Stoeckel et al, 2008).…”
Section: Introductionmentioning
confidence: 86%